Cambodia : 2019 Article IV Consultation; Press Release; Staff Report; and Statement by the Executive Director for Cambodia. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Cambodia discusses stable macroeconomic environment, strong growth and ongoing structural reforms have contributed to significant progress toward Sustainable Development Goals (SDGs). However, uncertainties including slower global growth and potential suspension of preferential market access under the Everything but Arms (EBA) scheme highlight the importance of maintaining macroeconomic stability while meeting still large development needs, addressing elevated financial sector vulnerabilities, and accelerating structural reforms. Continued strong revenue mobilization efforts and a prudent fiscal stance supported by restraining nondevelopment current spending will allow additional spending to address development needs. Expenditures should be oriented toward supporting inclusive growth through priority infrastructure investment, as well as health and education spending. Policies should be geared toward addressing sizeable spending needs to reach SDG targets in health, education and infrastructure, with support from the private sector and international donors. Accelerated implementation of structural reforms is needed to remove structural constraints to growth, correct external imbalances, address governance and corruption weaknesses and promote sustainable and inclusive development.